2019
DOI: 10.1016/j.polar.2019.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Weather conditions and warm air masses during active fire-periods in boreal forests

Abstract: Weather conditions for concurrent widespread fires in boreal forests were examined by various weather maps and temperature charts. The four study regions in boreal forests are three in East Siberia and one in Alaska. We applied preliminary analysis method for Sakha proposed by the authors to show the effectiveness of our approach. More than 12 very active fire-periods were identified from satellite hotspot data. Analysis results clearly showed fires during all active fire-periods became very active as warm air… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 23 publications
2
33
1
Order By: Relevance
“…3). This was consistent with the observation that subsidence of the air is higher at the ridge edges, leading to more severe fire conditions through higher rates of fuel drying and stronger surface winds, both promoting fire spread (Fauria and Johnson, 2006;Hayasaka et al, 2019) and possibly also lightning activity (Price, 2009). We did not reveal a century-long trend in the synchrony of LFY occurrence across EBZ and, similarly, no trend was visible for the MDC values indicative of the periods with strong fire hazard (Fig.…”
Section: Regional Patterns Of Fire Activity Within Ebz and Its Climatic Controlssupporting
confidence: 88%
“…3). This was consistent with the observation that subsidence of the air is higher at the ridge edges, leading to more severe fire conditions through higher rates of fuel drying and stronger surface winds, both promoting fire spread (Fauria and Johnson, 2006;Hayasaka et al, 2019) and possibly also lightning activity (Price, 2009). We did not reveal a century-long trend in the synchrony of LFY occurrence across EBZ and, similarly, no trend was visible for the MDC values indicative of the periods with strong fire hazard (Fig.…”
Section: Regional Patterns Of Fire Activity Within Ebz and Its Climatic Controlssupporting
confidence: 88%
“…Subsequently, we performed a daily fire analysis using daily hotspot (HS) data and weather maps, including temperature and wind, to understand fire weather during the active fire-period in eastern Siberia and Alaska. Our analysis results [26][27][28] clearly showed that fires during all active-fire periods became very active as warm air masses (cTe: continental temperate [29]) from the south approached the four study regions. These movements of warm air masses were mainly related to the meandering of large westerlies.…”
Section: Introductionmentioning
confidence: 99%
“…These movements of warm air masses were mainly related to the meandering of large westerlies. Strong wind conditions occurred when warm and dry air masses were approaching, stagnating, and passing over southern Sakha under various weather conditions at lower air level [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is facilitated by an increase in the average annual air temperature and duration of growing season [2], an increase in frequency and intensity of weather anomalies associated with global climate change [3], affecting on natural physical environment and vegetation cover [4]. In this aspect, a very useful role in terms of preventing active fires is played by the developments of researchers based on information the detection of active hotspots from MODIS time-series dataset of low resolution (Terra and Aqua satellites) [5]. A new approach to predictive assessment of fires [6] is based on a comprehensive analysis of data on detection of hotspots and baric topography maps at levels 925, 850, and 500 hPa, constructed from NCEP and NCAR reanalysis data [7].…”
Section: Introductionmentioning
confidence: 99%